Pengaruh Kualitas Pelayanan, Prosedur Kredit dan Jaminan Terhadap Keputusan Nasabah Mengambil Kredit Pada Koperasi di Desa Pejeng Kangin - I Kadek Joni Artana; I Putu Deddy Samtika Putra; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2026)
This study aims to explore the influence pertaining to service quality, credit procedures, and collateral on members' decissions to apply for loans at cooperatives in Pejeng Kangin Village, Tampaksiring District, Gianyar Regency. The sample of 76 respondents determined using the Slovin formula and random sampling techniques. The results showed that service quality, credit procedures, and collateral had a positive and significant influence on members' decisions to take/give loans. The adjusted R²a value of 0.617 indicates that these three variables explain 61.7% of the variation in members' decisions, while the remainder is influenced by other factors outside this study. The findings of this study highlight that improving service quality, simplifying procedures, and providing flexible collateral requirements are important factors in encouraging cooperative members to utilize loan services.